Social and cultural impacts of tourism and the effects on local perceptions towards homestay programme - Donny Sita, S.E.; Mohd Nor, N.A. (2014)
Research on local perceptions of tourism impacts is important to enhance the growth and the sustainability of tourism through thorough understanding of the inevitable tourism impacts it has on local peoples‘ lives.This research evaluates the local perceptions of social and cultural impacts of tourism based on the frequency in communication with tourists.This research was conducted in Kampung Benuk Homestay (KBH), Kuching.The locals, who consist of heterogeneous groups, have different degrees of contact with tourists and this research shows that the degrees of contact influence the perceptions they have on tourism development.The extent of their support (or restriction) toward additional tourism development can also be determined from their perceptions of tourism impacts.A qualitative approach was applied in this research. A total of 12 respondents comprised of four respondents in each group: 1) High contact, 2) Medium contact, and 3) Low contact, were face-to-face interviewed. Data from these semi-structured interviews were then analysed manually using the Microsoft Word 2010.The findings from this research indicated that "High contact‘ respondents perceived the homestay programme positively and supported for additional tourism development.In contrast, the ‗Medium contact‘ respondents were negative towards the programme and perceived more tourism costs than benefits.The "Low contact‘ respondents were rather positive, even though they did not participate in the programme and thus, were both supporting and restricting the additional tourism development.These findings contribute to the planning and policy of a community-based homestay programme.